A novel human Cdh1 mutation impairs anaphase promoting complex/cyclosome activity resulting in microcephaly, psychomotor retardation, and epilepsy - Rodríguez, Cristina; Sánchez‐Morán, Irene; Álvarez, Sara; Tirado, Pilar; Fernández‐Mayoralas, Daniel M.; Calleja‐Pérez, Beatriz; Almeida, Ángeles; Fernández‐Jaén, Alberto (Journal of neurochemistry, 2019)
The Fizzy‐related protein 1 (Fzr1) gene encodes Cdh1 protein, a coactivator of the E3 ubiquitin ligase anaphase‐promoting complex/cyclosome (APC/C). Previously, we found that genetic ablation of Fzr1 promotes the death of neural progenitor cells leading to neurogenesis impairment and microcephaly in mouse. To ascertain the possible translation of these findings in humans, we searched for mutations in the Fzr1 gene in 390 whole exomes sequenced in trio in individuals showing neurodevelopmental disorders compatible with a genetic origin. We found a novel missense (p.Asp187Gly) Fzr1 gene mutation (c.560A>G) in a heterozygous state in a 4‐year‐old boy, born from non‐consanguineous Spanish parents, who presents with severe antenatal microcephaly, psychomotor retardation, and refractory epilepsy. Cdh1 protein levels in leucocytes isolated from the patient were significantly lower than those found in his parents. Expression of the Asp187Gly mutant form of Cdh1 in human embryonic kidney 293T cells produced less Cdh1 protein and APC/C activity, resulting in altered cell cycle distribution when compared with cells expressing wild‐type Cdh1. Furthermore, ectopic expression of the Asp187Gly mutant form of Cdh1 in cortical progenitor cells in primary culture failed to abolish the enlargement of the replicative phase caused by knockout of endogenous Cdh1. These results indicate that the loss of function of APC/C‐Cdh1 caused by Cdh1 Asp187Gly mutation is a new cause of prenatal microcephaly, psychomotor retardation, and severe epilepsy. Read the Editorial Highlight for this article on page 8. Cover Image for this issue: doi: 10.1111/jnc.14524. We previously found that the anaphase promoting complex/cyclosome (APC/C) inactivation, by deletion of its activator Cdh1, promotes microcephaly in mouse. Here, we describe a de novo Cdh1 mutation (p.Asp187Gly) in a 4‐year‐old boy with prenatal microcephaly, psychomotor retardation, and epilepsy. Functional studies in the patient leukocytes, in a human cell line and in mouse neural precursor cells reveal that the Asp187Gly mutation results in decreased Cdh1 protein abundance, likely due to nuclear degradation, leading to APC/C inactivation. Thus, Cdh1 Asp187Gly mutation is herein identified as a novel cause of APC/C‐Cdh1 inactivation triggering prenatal microcephaly, psychomotor retardation, and severe epilepsy in human. Read the Editorial Highlight for this article on page 8. Cover Image for this issue: doi: 10.1111/jnc.14524. Open Science: This manuscript was awarded with the Open Materials Badge For more information see: https://cos.io/our-services/open-science-badges/